A new methodology to model and simulate microgrids operating in low latitude countries. (January 2019) - Aristizábal, Andrés Julián; Herrera, Jorge; Castaneda, Mónica; Zapata, Sebastian; Ospina, Daniel; Banguero, Edison
Abstract: Energy microgrids have acquired great importance recently thanks to their main characteristics: decentralized generation, use of renewable energy sources in a distributed way, energy storage capacities and the possibility of controlling and managing the use of power flows. This makes the microgrids an excellent option to reduce losses in the transmission and distribution lines and to reduce the use and dependence on fossil fuels worldwide. This article presents a methodology for designing and simulating renewable energy microgrids to operate in countries located near the equator. For this, several mathematical models are proposed for the different components of a microgrid: photovoltaic generator, wind turbine, battery bank and inverter for connection to the electricity grid. Solar and wind resources of five Colombian cities at low latitudes are analyzed: Barranquilla, Santa Marta, Cartagena, Riohacha and Lorica; through NASA's satellite measurement databases. Through the use of neural networks, microgrids are modeled to meet the monthly energy demand of residential users in the proposed cities. The power curves, energy, performance factor and performance variables of the designed systems are presented and discussed. The results allow to validate the excellent energy option represented by microgrids for low-latitude countries, with good rates of solar radiation and wind speed.